(untitled) (International Journal of Engineering and Computer Science, 2015)
Now a day’s cloud based systems are getting more attraction as the number of users data is rapidly increasing. The organizations are worried about the storing of data and its security. The Role Based Encryption Scheme (RBAC) provides a way to the users for managing and sharing the data in a cloud. The RBAC will combine cryptographic techniques and access controls to secure the data. With the use of these techniques the owner of data will encrypt the data in such a way that the appropriate user of the role can decrypt and view the data. In this paper we provide a hybrid cloud in which the organization data will be stored in a private cloud while the authorized users are allowed to store their data in public cloud. The role based encryption (RBE) scheme will be helpful to solve the security issue. In this paper we are integrating the RBE scheme using the AES algorithm for encryption and decryption of the data. The paper also shows the mathematical model for calculating the trust of the user. This can be used by the owner when he wants to upload any data on the cloud.